Varieties of austerity / Heather Whiteside, Stephen McBride and Bryan M. Evans. - Whiteside, Heather, 1982-; McBride, Stephen; Evans, Bryan M., 1960- (Bristol University Press, 2021)
Identifying continuity and variety in crisis-driven austerity restructuring across Canada, Denmark, Ireland and Spain, this important book uncovers how austerity can be categorized into different dynamic types, and exposes the economic, social and political implications of the varieties of austerity.